Response of tomato wilt pathogen Ralstonia solanacearum to the volatile organic compounds produced by a biocontrol strain Bacillus amyloliquefaciens SQR-9 - Raza, Waseem; Ling, Ning; Yang, Liudong; Huang, Qiwei; Shen, Qirong (Scientific reports, 2016)
It is important to study the response of plant pathogens to the antibiosis traits of biocontrol microbes to design the efficient biocontrol strategies. In this study, we evaluated the role of volatile organic compounds (VOCs) produced by a biocontrol strain Bacillus amyloliquefaciens SQR-9 on the growth and virulence traits of tomato wilt pathogen Ralstonia solanacearum (RS). The VOCs of SQR-9 significantly inhibited the growth of RS on agar medium and in soil. In addition, the VOCs significantly inhibited the motility traits, production of antioxidant enzymes and exopolysaccharides, biofilm formation and tomato root colonization by RS. The strain SQR-9 produced 22 VOCs, but only nine VOCs showed 1–11% antibacterial activity against RS in their corresponding amounts; however, the consortium of all VOCs showed 70% growth inhibition of RS. The proteomics analysis showed that the VOCs of SQR-9 downregulated RS proteins related to the antioxidant activity, virulence, carbohydrate and amino acid metabolism, protein folding and translation, while the proteins involved in the ABC transporter system, amino acid synthesis, detoxification of aldehydes and ketones, methylation, protein translation and folding, and energy transfer were upregulated. This study describes the significance and effectiveness of VOCs produced by a biocontrol strain against tomato wilt pathogen.